Prediction of patellofemoral instability by quantitative ultrasound elastography device: a feasibility study - Lan Zeng; Li Zhang; Jiuyi Ma; Jianqiu Huang; Yang Sun (BMC Musculoskeletal Disorders)
Abstract Background This study evaluated the reproducibility of shear modulus (SM) measurements of the quadriceps muscle in straight and bent knee positions using a quantitative ultrasound elastography device and explored its potential in predicting patellofemoral instability (PFI). Methods The study included 13 healthy subjects and 34 patients with anterior knee pain. Among the 68 legs of 34 patients, 23 had lateral patellar tilt and 9 had patella alta. The SM of the lateral femoral muscle (LFM), medial femoral muscle (MFM), and rectus femoris muscle (RFM) was measured in both knee straight and bent positions using a quantitative ultrasound device. Intra-observer and inter-observer reliability were assessed by intraclass correlation coefficient (ICC), and the performance of SM values in predicting lateral patellar tilt and patella alta was analyzed using receiver operating characteristic (ROC) curves. Results SM measurements of the LFM, MFM, and RFM showed good to excellent intra- and inter-observer reliability (ICC = 0.770–0.993, all P < 0.001). The group with lateral patellar tilt showed significantly higher SM(LFM)bent, SM(L/M)bent, and SM(LFM)bent−straight compared to the group without lateral patellar tilt. Similarly, SM(RFM)bent and SM(RFM)bent−straight of the group with patella alta were significantly higher than those of the group without patella alta. ROC analysis showed that SM(LFM)bent and SM(LFM)bent−straight were highly effective in predicting lateral patellar tilt, while SM(RFM)bent and SM(RFM)bent−straight were effective for predicting patella alta. Conclusions Quantitative elastography ultrasound for measuring quadriceps muscle SM offers a reliable, noninvasive method for assessing mechanical stress around the knee, providing high predictive accuracy for PFI.